2016
DOI: 10.3390/nu8030107
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Gallotannin-Enriched Extract Isolated from Galla Rhois against CCl4-Induced Hepatotoxicity in ICR Mice

Abstract: To investigate the toxicity, protective effects, and action mechanism of gallotannin-enriched extracts isolated from Galla Rhois (GEGR) against carbon tetrachloride (CCl4)-induced hepatotoxicity in Institute for Cancer Research (ICR) mice, alterations in serum biochemical indicators, histopathological structure, antioxidative status, hepatic apoptosis-related proteins, and liver fibrosis regulating factors were measured in mice pretreated with GEGR for five days before CCl4 injection. The GEGR/CCl4 treated gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…However, strawberry juice supplementation strongly decreased transaminases enzyme in the serum. These findings were consistent with those of many previous studies that showed administration of several antioxidant mixtures or herbal medicines significantly declined the levels of serum marker enzymes in CCl 4 treated animals as mentioned by Go et al ( 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, strawberry juice supplementation strongly decreased transaminases enzyme in the serum. These findings were consistent with those of many previous studies that showed administration of several antioxidant mixtures or herbal medicines significantly declined the levels of serum marker enzymes in CCl 4 treated animals as mentioned by Go et al ( 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…Hepatic fibrosis, which is a histological hallmark of chronic liver disease, is characterized by excessive accumulation of connective tissue in the liver and considered an indicator of persistent or progressive hepatic injury 26 . In a previous study, dense staining of an excessive accumulation of collagen that expanded into the portal triads was observed in a Vehicle+CCl 4 -treated group compared with a non-treated group 27 . To investigate the protective effects of EtSCT against CCl 4 -induced hepatic fibrosis, samples were evaluated for changes in collagen and MMPs expression, and TGF-β1 signaling pathways were observed in the liver tissue of the subset groups.…”
Section: Resultsmentioning
confidence: 76%
“…JGJ consists of specific herbs which have detoxifying effects. Galla Rhois is the gall produced by the aphid, Schlechtendalia chinensis (Bell), on the leaves of Rhus chinensis, and contains about 50-90% gallotannin, which has antioxidant and hepatoprotective properties [32,33]. Cremastrae Tuber is the tuber of Cremastra appendiculata M. and contains glucomannan and colchicine, which have anti-inflammatory and anticancer properties [34,35].…”
Section: Discussionmentioning
confidence: 99%